Effect of a glass ionomer cement and a fluoride varnish on cross-sectional microhardness values of artificial occlusal caries: In vitro study - MWM Souchois; R S Vieira (Wolters Kluwer Medknow Publications, 2012)
Context: Active white spot lesions (WSLs) are a great concern to clinicians. Aims: This in vitro experiment analyzed cross-sectional microhardness (CSMH) values of occlusal artificially induced active WSLs (control groups D/A, D/B and D/C) along with experimental groups where these lesions were: Exposed to an artificial high risk cariogenic challenge (HRCC) using pH cycling; treated with a glass ionomer cement (GIC) and then exposed to artificial HRCC; or a fluoride varnish (FV) and afterwards submitted to the same artificial HRCC. Materials and Methods: Sixty unerupted human third molars were sectioned buccolingually on the occlusal surface and demineralized for 42 days. One half of each tooth was allocated to control groups (D/A, D/B, and D/C) and the other were used as test groups: A (pH cycling); B (GIC + pH cycling); and C (FV + pH cycling). CSMH test was performed for sound, demineralized, and treated specimens. Statistical Analysis Used: Different depths for CSMH values did not have a normal distribution (Kolmogrov-Smirnov test) and for that matter Wilcoxon and T Test were applied (significance level of 5%). Results: Mean depth of the lesion was 120 μm. A number of samples both in the test groups (n = 37) as in control groups (n = 47) had a lower Knoo p value (softening) or surface erosion. Comparisons between control and test groups only showed statistical difference at a depth 140 μm (P = 0.010) in control group D/A and for test group B at 20 μm (P = 0.004) and at 40 μm (P = 0.007). Conclusions: This in vitro study demonstrated that the use of GIC over an artificial active WSLs and exposed to an artificially HRCC setting tend to express some effect in increased surface KHN values.